2019
DOI: 10.3390/nu11122904
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Calebin A, a Component of Curcuma Longa Suppresses NF-κB Mediated Proliferation, Invasion and Metastasis of Human Colorectal Cancer Induced by TNF-β (Lymphotoxin)

Abstract: Objective: Natural polyphenol Calebin A has been recently discovered as a novel derivate from turmeric with anti-cancer potential. Pro-inflammatory cytokine TNF-β (lymphotoxin α) is a stimulant for cancer cell malignity via activation of NF-κB pathway, also in colorectal cancer (CRC). Here, we investigated the potential of Calebin A to suppress TNF-β-induced NF-κB signalling in CRC. Materials and Methods: Three distinct CRC cell lines (HCT116, RKO, SW480) were treated in monolayer or 3-dimensional alginate cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 69 publications
3
54
0
Order By: Relevance
“…We have previously demonstrated that TNF-β/NF-κB-induced CRC proliferation, chemoresistance and tumor stem cell promotion was suppressed by natural substances such as resveratrol [16,17]. Furthermore, in a previous study on CRC, we showed the potential of Calebin A on suppressing-TNF-β-induced inflammatory signaling, blocking proliferation, migration and invasion of CRC cells [18], emphasizing the promising of natural substances on targeting TNF-β/NF-κB signaling axis.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…We have previously demonstrated that TNF-β/NF-κB-induced CRC proliferation, chemoresistance and tumor stem cell promotion was suppressed by natural substances such as resveratrol [16,17]. Furthermore, in a previous study on CRC, we showed the potential of Calebin A on suppressing-TNF-β-induced inflammatory signaling, blocking proliferation, migration and invasion of CRC cells [18], emphasizing the promising of natural substances on targeting TNF-β/NF-κB signaling axis.…”
Section: Discussionmentioning
confidence: 84%
“…To prevent treatment failure, co-treatment with non-toxic dietary natural anti-cancer agents that possess the capacity to chemosensitize and treat these resistant tumors have great potential [39]. Calebin A, a naturally occurring compound (an ingredient of natural turmeric) has been suggested to have anti-cancer capacity in various solid cancer cells [18,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations